The Effect of the Problem-Based Learning Model on the Skills of Writing Recount Texts of High School Students - Hijerah, Hijerah; Iswatiningsih, Daroe; Inganah, Siti (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to examine the effect of the Problem-Based Learning (PBL) model on the recount text writing skills of Grade X students at Muhammadiyah 1 Senior High School, Makassar. The study combined qualitative exploration with a quasi-experimental design to examine the impact of the Problem-Based Learning (PBL) model on students’ recount writing skills. Fifty Class X students participated, with data collected through writing tests and observations and analyzed using independent and paired samples t-tests. The results showed that PBL significantly improved students’ writing performance, as indicated by a p-value < 0.05. The study was conducted from January to June 2025, with fifty Grade X students selected through total sampling. Overall, this research seeks to determine whether PBL can significantly improve students’ ability to write recount texts within a real classroom setting. The results showed that the application of the Problem-Based Learning (PBL) model effectively improved the recount writing skills of grade X students at Muhammadiyah 1 Senior High School, Makassar. This model encourages active participation, critical thinking, and collaborative learning, resulting in significant improvements in students' writing skills, particularly in text organization, past tense usage, vocabulary selection, coherence, and idea development. Furthermore, PBL enhances students' motivation and engagement by connecting writing tasks to real-life contexts, making the learning experience more meaningful. Therefore, the PBL model can be considered an effective and innovative approach to improving students' writing competence and overall literacy skills.